Remote Ultrasonic Imaging of a Wire Arc Additive Manufactured Ti-6Al-4V Component using Laser Induced Phased Array - Lukacs, Peter; Williams, Stewart; Davis, Geo; MacLeod, Charles; Stratoudaki, Theodosia; Gachagan, Anthony (Cranfield University, 2021)
Supporting dataset for the publication: "Remote Ultrasonic Imaging of a Wire Arc Additive Manufactured Ti-6Al-4V Component using Laser Induced Phased Array".The file contains all the signals used to produce the images in the paper, using information mentioned in the paper, e.g. pitch and filter centre frequency.
Keywords: 'laser ultrasonics'; 'ultrasonic imaging'; 'additive manufacturing'; 'remote sensing'; 'Additive Manufacturing'; 'Photogrammetry and Remote Sensing'